Respuesta :

Answer:okay so if x=2 .. then

There you go hope it helps you

when it says for all the values... it usually means like any number can replace x

Ver imagen Аноним

Answer:

Step-by-step explanation:

x² + 6x + 18 > 2 - (1/2) x

Multiplying through by 2

2x² + 12x + 36 > 4 -x

2x² + 12x - x + 36 - 4 > 0

2x² + 11x + 32 > 0

Using  Almighty formula

x = (-b ± √b² - 4ac) ÷ 2a

Therefore

a = 2, b = 11, c = 32

x = (-11 ± √(11)² - (4 × 2 × 32)) ÷ (2 × 2) > 0

x = (-11 ± √121 - 256) ÷ 4 > 0

x = (-11 ± √-135) ÷ 4 > 0